Poco-poco implementation of the death penalty for corruptors in the time of force majeure - Amalia Syauket; Erwin Owan Hermansyah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Under the legal basis, a pandemic is included in the time of force majeure,